1970
DOI: 10.1111/j.1365-2494.1970.tb00618.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Behaviour and Weight Changes in Calves Turned Out to Pasture

Abstract: Two studies are described in which the behaviour of 24 seven-month-old Friesian steer calves was observed. The first study (Gl) was undertaken at the time of turnout to pasture, and the second (G2) 5 days later. The calves appeared to adapt rapidly to the change in environment, though in study Gl grazing was frequently interrupted. In study G2 the calves showed normal behaviour patterns and spent a total of 4 25 hours grazing.There was a positive correlation between age and weight at turnout and time spent gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This lower growth prior to turning out in 1977 seems to have led to some compensatory growth at grass since the overall gains from birth to housing were 0-63 kg/day and 0-62 kg/day for 1976 and 1977 respectively. Wilkinson & Cumberland (1970) examined the relationship between growth rate in the pre-grazing period and performance during the first month at grass and the data indicated that cattle tend to compensate for slower growth prior to turning out. A similar fact was reported by Baker & Baker (1965) and by Forbes, Raven & Robinson (1966).…”
Section: Discussionmentioning
confidence: 99%
“…This lower growth prior to turning out in 1977 seems to have led to some compensatory growth at grass since the overall gains from birth to housing were 0-63 kg/day and 0-62 kg/day for 1976 and 1977 respectively. Wilkinson & Cumberland (1970) examined the relationship between growth rate in the pre-grazing period and performance during the first month at grass and the data indicated that cattle tend to compensate for slower growth prior to turning out. A similar fact was reported by Baker & Baker (1965) and by Forbes, Raven & Robinson (1966).…”
Section: Discussionmentioning
confidence: 99%